The rs4646 and rs12592697 Polymorphisms in CYP19A1 Are Associated with Disease Progression among Patients with Breast Cancer from Different Racial/Ethnic Backgrounds - Armamento-Villareal, Reina; Shah, Vallabh O.; Aguirre, Lina E.; Meisner, Angela L. W.; Qualls, Clifford; Royce, Melanie E. (Frontiers in Genetics, 2016)
Given the racial/ethnic disparities in breast cancer, we evaluated the association between CYP19A1 single nucleotide polymorphisms (SNPs) on disease progression in women with breast cancer from different racial/ethnic backgrounds. This is a cross-sectional analysis of data from 327 women with breast cancer in the Expanded Breast Cancer Registry program of the University of New Mexico. Stored DNA samples were analyzed for CYP19A1 SNPs using a custom designed microarray panel. Genotype-phenotype correlations were analyzed. Of the 384 SNPs, 2 were associated with clinically significant outcomes, the rs4646 and rs12592697. The T allele for the rs4646 was associated with advanced stage of the disease at the time of presentation (odds ratio [OR]:1.8, confidence intervals [CI]: 1.05-3.13, p<0.05) and a more progressive disease (OR: 2.1 [CI: 1.1-4.0], p=0.04). For the rs12592697, the variant T allele was more frequent in Hispanic women and associated with a more progressive disease (OR: 2.05 [CI: 1.0-4.0], p=0.04). However, further analysis according to menopausal status showed that the association between these 2 SNPs with disease progression or the stage at diagnosis are confined only to postmenopausal women. The odds ratios of disease progression among postmenopausal women carrying the T allele for the rs4646 and rs12592697 are 3.05 (1.21, 7.74, p=0.02) and 3.80 (1.24, 11.6, p=0.02), respectively. Regardless, differences in disease progression among the different genotypes for both SNPs disappeared after adjustment for treatment. In summary, the rs4646 and the rs12592697 SNPs in CYP19A1 are associated with differences in disease progression in postmenopausal women. However, treatment appears to mitigate the differences in genetic risk. ClinicalTrials.govs Identifier: NCT00322894(https://clinicaltrials.gov/ct2/show/NCT00322894?term=new+mexico+breast+cancer+registry&rank=1)